All-inorganic CsPbBr3 perovskite: a promising choice for photovoltaics. Issue 2 (4th January 2021) - Ullah, Saad; Wang, Jiaming; Yang, Peixin; Liu, Linlin; Yang, Shi-E.; Xia, Tianyu; Guo, Haizhong; Chen, Yongsheng
Abstract : In recent years, inorganic CsPbBr3 -based perovskites have accomplished considerable progress owing to their superior stability under harsh humid environment. Abstract : In recent years, inorganic CsPbBr3 -based perovskites have accomplished considerable progress owing to their superior stability under harsh humid environment. The power conversion efficiency (PCE) of CsPbBr3 perovskite solar cells (PSCs) has seen an unprecedented development from 5.74% to 10.91% with the improvement of the CsPbBr3 crystal quality. Despite extensive research efforts, the device efficiency of the CsPbBr3 -based PSCs still lags behind that of other hybrid perovskite materials. Therefore, there is a significant interest in further boosting the performance of all-inorganic CsPbBr3 PSCs by the synergic optimization of films and device interfaces. In this review, we have discussed and summarized recent advances and methodologies related to CsPbBr3 films and PSCs. Furthermore, we discuss different fabrication strategies such as solution-based and vapor-based methods and their influence on the properties of CsPbBr3, particularly the morphology of films. Moreover, the timeline of improvement of the device efficiency from 2015 to 2020 is comprehensively addressed and developments are clearly sorted out by addressing critical factors influencing the photovoltaic performance. We further highlight state-of-the-art engineering strategies for CsPbBr3 PSCs that facilitate the crystallization control, charge extraction, suppression of charge recombination, and defect passivation in a systematic manner. At the end of the review, the summary and perspectives are presented along with beneficial guidelines for developing highly efficient and stable CsPbBr3 PSCs.